The Effect of Ingredients Mixing Sequence in Rubber Compounding upon Vulcanization Kinetics of Natural Rubber: An Autocatalytic Model Study - Abu Hasan; Rochmadi Rochmadi; Hary Sulistyo; Suharto Honggokusumo (Universitas Gadjah Mada, 2018)
This study examined the effect of ingredients mixing sequence to the vulcanization kinetics of natural rubber. The effects of mixing temperature, vulcanization temperature, and the carbon black type upon the kinetics were also studied by using rheography and an autocatalysis reaction model approach. The results showed that this model is good in providing information on vulcanization reaction kinetics of natural rubber. High vulcanization temperature resulted in high reaction rate constant. The more black carbon mixed at the beginning of the rubber mixing process, the higher reaction rate constant would be. The mixing of carbon black and rubber chemicals mixed into the rubber subsequently resulted in the higher reaction rate constant compared with that of simultaneously.